KAJIAN PSIKOLOGI WANITA TOKOH UTAMA NOVEL AIR MATA TUHAN KARYA AGUK IRAWAN M.N. - Zeni Ernawati; Sri Mariati; Titik Maslikatin (Fakultas Ilmu Budaya Universitas Jember, 2017)
AbstractA novel entitled Air Mata Tuhan as a study of woman psychology was focused on the main character. This research aimed to know the forms of women’s personality, and to describe the linkage between structural elements and psychology aspect contained on the main character in the Novel entitled Air Mata Tuhan written by Aguk Irawan M.N. The used research method was qualitative by using literature study. The data contained in the Novel entitled Air Mata Tuhan were also analyzed. The research result indicated that structural elements included title, theme, characterization, character, and conflict has the linkage. The analysis of woman psychology showed that (1) the woman characteristic was beauty included beauty of inside and outside, tenderness, humility, nurturing, easily disappointed and rise up again; (2) woman and family, included woman as a wife, woman as a partner of life; and (3) woman and depression. Those characteristics were belonged to the main character in the Novel entitled Air MataTuhan named Fisha.